A pathologist's survey on the reporting of sessile serrated adenomas/polyps. Issue 5 (7th January 2014) - Chetty, Runjan; Bateman, Adrian C; Torlakovic, Emina; Wang, Lai Mun; Gill, Pelvender; Al-Badri, Adnan; Arends, Mark; Biddlestone, Leigh; Burroughs, Susan; Carey, Frank; Cowlishaw, David; Crowther, Stephen; et al.
Abstract : Aim: The purpose of this survey was to ascertain reporting habits of pathologists towards sessile serrated adenomas/polyps (SSA/P). Methods: A questionnaire designed to highlight diagnostic criteria, approach and clinical implications of SSA/P was circulated electronically to 45 pathologists in the UK and North America. Results: Forty-three of 45 pathologists agreed to participate. The vast majority (88%) had a special interest in gastrointestinal (GI) pathology, had great exposure to GI polyps in general with 40% diagnosing SSA/P at least once a week if not more, abnormal architecture was thought by all participants to be histologically diagnostic, and 11% would make the diagnosis if a single diagnostic histological feature was present in one crypt only, while a further 19% would diagnose SSA/P in one crypt if more than one diagnostic feature was present. The vast majority agreed that deeper sections were useful and 88% did not feel proliferation markers were useful. More than one-third did not know whether, or did not feel that, their clinicians were aware of the implications of SSA/P. Conclusions: 98% of pathologists surveyed are aware that SSA/P is a precursor lesion to colorectal cancer, the majority agree on diagnostic criteria, and a significant number feel that there needs to be greater communication and awareness among pathologists and gastroenterologists about SSA/P.